Influence of Task Commitment, Learning Styles, and Learning Strategies on the Reading Comprehension of English Literature among Psychology Students at UIN Syarif Hidayatullah Jakarta - Hamidah, Hamidah; Huzaziah, Euis; Fitri, Ade Zoraya; Oktavia, Oktavia (IJBLE Scientific Publications Community Inc., 2025)
This study aims to examine the influence of task commitment, learning strategies, and learning styles on the reading comprehension of English literature among psychology students at UIN Syarif Hidayatullah Jakarta. The study involved 200 participants (41 males and 159 females). The data collection instrument used was a Likert-scale questionnaire comprising four measurement scales: Reading Comprehension, Task Commitment, Learning Strategies, and Learning Styles. Instrument testing was conducted using Confirmatory Factor Analysis (CFA) with SPSS 20. Data analysis employed multiple linear regression using SPSS 20 for Windows. The results revealed that task commitment, learning strategies, and learning styles significantly influence students’ reading comprehension of English literature. Specifically, task commitment, cognitive learning strategies, and metacognitive strategies had a significant effect on reading comprehension, while learning styles did not demonstrate a significant impact.